-8x-y=-6

Simple and best practice solution for -8x-y=-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8x-y=-6 equation:


Simplifying
-8x + -1y = -6

Solving
-8x + -1y = -6

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'y' to each side of the equation.
-8x + -1y + y = -6 + y

Combine like terms: -1y + y = 0
-8x + 0 = -6 + y
-8x = -6 + y

Divide each side by '-8'.
x = 0.75 + -0.125y

Simplifying
x = 0.75 + -0.125y

See similar equations:

| 0.3x+3.8=x | | 33.8-32= | | -9x+3y=9 | | -7x+5=-16 | | 1/9c+36=7/9c+5 | | -2+x/3=5 | | -30=5a | | 6(7b-7)=-4+4b | | y=0.8x+3 | | 2/3(12-3h)=h | | 7d+4d-6d+2-8=2d | | 3y=-4x+12 | | -7(1+2x)=23-8x | | -3(3x-6)-18=-3(5s+5)-4 | | -4(1+7m)=30+6m | | n=250/100(2) | | 4(k-9)+18=6 | | -8a^2-6a+9=0 | | -y+2=0 | | 4n+4/2=-13 | | y=0.9x+3 | | 1.92+.04x=1.92+.08x | | 2x+6/x+3 | | 25X+6-27X=5-9 | | 3(z-2)=2(z+7) | | -7(3n+2)=-8n+38 | | 7+36=-11 | | 10x-12y=2 | | 5.3m-6=-27.2 | | 5y+6=4y-7 | | .16(12)+.04x=.08(24+x) | | n-4-9=0 |

Equations solver categories